2015
DOI: 10.1111/apt.13378
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: instruments to assess abdominal pain in irritable bowel syndrome

Abstract: SUMMARY BackgroundConsensus on standard methods to assess chronic abdominal pain in patients with irritable bowel syndrome (IBS) is currently lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 150 publications
0
50
0
Order By: Relevance
“…Abdominal pain was measured by a 0‐100 mm visual analog scale in all participants. The VAS is a simple, fast, and patient‐friendly method to measure the intensity of abdominal pain by a 100 mm horizontal line that is fixed between 0 mm indicating “no pain at all” and 100 mm indicating “worst pain tolerable” . We asked all participants only about current abdominal pain in order to avoid any recall bias, as it is known that longer reference periods are associated with higher recall bias.…”
Section: Methodsmentioning
confidence: 99%
“…Abdominal pain was measured by a 0‐100 mm visual analog scale in all participants. The VAS is a simple, fast, and patient‐friendly method to measure the intensity of abdominal pain by a 100 mm horizontal line that is fixed between 0 mm indicating “no pain at all” and 100 mm indicating “worst pain tolerable” . We asked all participants only about current abdominal pain in order to avoid any recall bias, as it is known that longer reference periods are associated with higher recall bias.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of instruments to assess abdominal pain in IBS can be found elsewhere 27 . Perhaps the simplest method is the 10-point Numeric Rating Scale (NRS), in which patients rate their abdominal pain severity from 1 (no pain) to 10 (the worst pain imaginable).…”
Section: Abdominal Painmentioning
confidence: 99%
“…About 40–50% of adults abdominal pain is thought to be of functional origin, and in children this increases to 80–90% 2 5. Only 1.6% of children with a diagnosis of NSAP were later found to have an identifiable organic cause.…”
Section: Commentarymentioning
confidence: 99%